Enhancing Administrative Texts Through Cohesive Devices and Narrative Elements - Ly Ngoc, Toan (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study aims to shed light on how the combination of cohesive devices (henceforth CDs) and narrative elements (NEs) contributes to developing the coherence and clarity of administrative texts (ATs). While CDs and NEs were constantly treated as separate elements in previous studies, this research delves into their interaction as complementary strategies within ATs. Quantitative content analysis was employed to analyze 20 Vietnamese ATs, the results show that when CDs (reference, conjunction, ellipsis, and substitution) are combined with NEs (processes, participants, and spatial-situational settings), they occupy a crucial role in constructing textual cohesion, thematic continuity, and systematic transparency. These compound linguistic elements improve reading competence. As a result, readers can retain information more effectively, and the formal tone of administrative texts becomes more reinforced. Moreover, the results suggest that merging structural and experiential meanings in ATs significantly enhances both clarity and reader engagement. Drawing upon systemic functional linguistics as its theoretical framework, this study improves both theoretical interpretation within discourse studies and practical implications for developing ATs. Building on these findings, this study develops an analytical framework for examining how the combination of NEs and CDs operates to achieve structural objectives. Future research can apply this model to other text types, which are characterized by clarity, integrity, and formal structure. In short, this research demonstrates the roles of CDs and NEs in the construction of coherent and accessible ATs.